Biochemical and clinical profiles of 52 Tunisian patients affected by Zellweger syndrome - Fahmi Nasrallah; Wiem Zidi; Moncef Feki; Samia Kacem; Neji Tebib; Naziha Kaabachi (Elsevier, 2017)
Background: Zellweger syndrome (ZS) is a peroxisome biogenesis disorder attributed to a mutation of the PEX genes family. The incidence of this disease in Africa and the Arab world remains unknown. This contribution is aimed at describing the clinical phenotype and biochemical features in Tunisian patients with ZS in order to improve the detection and management of this severe disorder. Methods: A total of 52 patients diagnosed with ZS and 60 age- and sex-matched healthy controls were included in this study. Patients were recruited during the past 21 years, and the diagnosis of ZS was based on clinical and biochemical characteristics. Plasma very long chain fatty acids (VLCFA) were analyzed using capillary gas chromatography. The estimated incidence of ZS was calculated using the HardyâWeinberg formula. Results: The estimated incidence of ZS is 1/15,898 in Tunisia. Age at diagnosis varied between 3 days and 18 months. Severe neurological syndrome, polymalformative features, and hepatodigestive signs were observed in 100%, 67.9%, and 32% of patients, respectively. Values for plasma C26:0 and C26:0/C22:0 and C24:0/C22:0 ratios were noticeably higher in ZS patients than in controls. Distributions of values were completely different for C26:0 (0.10â0.37 vs. 0.001â0.009), C26:0/C22:0 ratio (0.11â1.29 vs. 0.003â0.090), and C24:0/C22:0 ratio (1.03â3.18 vs. 0.4â0.90) in ZS patients versus controls, respectively. Conclusions: This study highlights the high incidence of ZS in Tunisia and the possibility of simple and reliable biochemical diagnosis, thus permitting early genetic counseling for families at risk. Key Words: gas chromatography, hypotonia, peroxisomal disorder, very long chain fatty acids, Zellweger syndrome